Adverse effect of topical methylsalicylate ointment on warfarin anticoagulation: an unrecognized potential hazard. Issue 775 (May 1990) - Yip, A. S.; Chow, W. H.; Tai, Y. T.; Cheung, K. L.
Abstract : The adverse effect of topical methylsalicylate ointment on warfarin anticoagulation is studied in 11 patients. All patients had an abnormally elevated international normalized ratio after significant usage of topical methylsalicylate ointment as obvious from both the clinical history and a positive blood level of salicylate. Out of the 11 patients, 3 had bleeding manifestation; 2 with bruises and 1 with gastrointestinal bleeding. It is concluded that topical methylsalicylate ointment should be prescribed with care to patients on warfarin and excessive usage is to be avoided since potentially dangerous drug interaction could occur.